Attributional Beliefs of Canadian Trainee Teachers toward Students with a Learning Disability - Woodcock, Stuart (Alberta Journal of Educational Research, 2014)
Teachers are one of the most important factors in successful inclusion of students with a learning disability in mainstream classrooms. Attitudes towards inclusion of certain students in classrooms have been mixed, and many attitudes are often developed during the pre-service training and early teaching years. This study investigated the attitudes of trainee teachers towards students with learning disabilities by analysing their attributional responses to hypothetical students. Accordingly, 181 graduating Canadian trainee teachers were surveyed and the results indicated that as students’ ability levels decrease, teachers’ sympathy levels rise, and the expectation of future failure increases. Moreover, as students’ expended efforts increase, the teacher feedback becomes more positive, the frustration decreases, the sympathy levels rise, and the expectation of future failure decreases. With regards to differences between students with and without a learning disability, as students’ ability levels increase the difference in trainee teachers’ sympathy level increases. Furthermore, as students’ expended efforts increase, the difference in teacher feedback given to students with and without a learning disability decreases, the difference in frustration and sympathy levels decrease, and the difference in expectations of future failure increases. Implications and recommendations for practice and research conclude the paper. Les enseignants représentent un des facteurs les plus importants pour une l’inclusion réussie des élèves avec des troubles d’apprentissage dans les salles de classe ordinaires. Les attitudes face à l’inclusion de certains étudiants dans les classes sont variées, et plusieurs d’entre elles se sont développées au cours de la formation d’enseignant et les premières années d’enseignement. Cette étude a analysé les biais d’attribution de stagiaires face à des élèves hypothétiques de sorte à étudier leurs attitudes relatives aux élèves ayant des difficultés d’apprentissage. Ainsi, une enquête auprès de 181 stagiaires canadiens au terme de leurs études a indiqué que plus les compétences des élèves baissent, plus les stagiaires éprouvent de la sympathie pour eux et plus ils s’attendent à ce que les élèves échouent. De plus, plus les élèves font des efforts, plus la rétroaction des stagiaires devient positive, plus la frustration diminue, plus les stagiaires éprouvent de la sympathie et moins ils anticipent un échec de la part des élèves. Quant aux différences entre les élèves sans trouble d’apprentissage et les élèves ayant un trouble d’apprentissage, plus les compétences des élèves augmentent, plus la différence dans le niveau de sympathie éprouvée par les stagiaires augmente. En outre, plus les élèves font des efforts, plus la différence dans la rétroaction des stagiaires offerte aux élèves avec et sans un trouble d’apprentissage diminue, plus la différence des niveaux de frustration et de sympathie diminue et plus la différence quant aux attentes relatives aux possibilités d’échec augmente. Des retombées de l’étude et des recommandations relatives à la pratique et la recherche viennent conclure l’article.